An Assessment of Trust in Medical Profession amongst People Residing in a Semi-Urban Area, Tamil Nadu (Indian Journal of Public Health Research & Development, 2020)
Introduction: The fundamental basis in health care system and relationship is Trust. Trust is a set of expectations that the health care provider will do the best for the patient.The word “Trust” has been in a state of crisis over the last decade in India particularly in medical profession. Unlimited and implicit access to health care system and medical information from a varied range of source helps patients in one way and in contrary to that it may also misinform and adversely affect “Trust” in medical profession. Objectives • To assess trust in medical profession among people (>18years ) residing in a semi urban area of TamilNadu. • To assess the factors affecting Trust in medical profession. Methodology: A community based cross-sectional study was conducted during February 2019 in Thirumazhisai , a semi-urban township in Chennai. 150 Men and Women above 18 years were included in the study. Data Collection was done using semi structured questionnaire. TMP(Trust in Medical Profession) scale was used to measure trust in medical profession. Result: 56.4% have good trust on Doctors and 44.33% have trust lower than the expected score based on TMP scale. Trust was higher among unemployed, women , people below poverty line , those not suffering from chronic illness though statistical association could be established only with socio economic status(p 0.04) and system of medicine followed (p 0.01). Conclusion: The trust in doctors have largely been reduced and hence understanding this would lead to better ways of responding to patients requests that preserve or enhance patients trust, leading to better outcomes.
Keywords: trust in medical profession, TMP scale, semi urban area.